2018
DOI: 10.1371/journal.pone.0209408
|View full text |Cite
|
Sign up to set email alerts
|

Protein engineering strategies for improving the selective methylation of target CpG sites by a dCas9-directed cytosine methyltransferase in bacteria

Abstract: Mammalian gene expression is a complex process regulated in part by CpG methylation. The ability to target methylation for de novo gene regulation could have therapeutic and research applications. We have previously developed a dCas9-MC/MN protein for targeting CpG methylation. dCas9-MC/MN is composed of an artificially split M.SssI methyltransferase (MC/MN), with the MC fragment fused to a nuclease-null CRISPR/Cas9 (dCas9). Guide RNAs directed dCas9-MC/MN to methylate target sites in E. coli and human cells b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…This contrast of good activity in the target methylation using the dCS system, but low activity in enzymatic essays with purified proteins, can be explained by the targeting and signal amplification effects of the SunTag. A similar approach was utilized by Xiong et al, who demonstrated site-specific DNA methylation in bacteria [41]. In this study, the authors used dCas9 with a split M.SssI methyltransferase and optimized the specificity by targeted mutagenesis of the DNA binding domain of M.SssI.…”
Section: Discussionmentioning
confidence: 97%
“…This contrast of good activity in the target methylation using the dCS system, but low activity in enzymatic essays with purified proteins, can be explained by the targeting and signal amplification effects of the SunTag. A similar approach was utilized by Xiong et al, who demonstrated site-specific DNA methylation in bacteria [41]. In this study, the authors used dCas9 with a split M.SssI methyltransferase and optimized the specificity by targeted mutagenesis of the DNA binding domain of M.SssI.…”
Section: Discussionmentioning
confidence: 97%
“…In addition to furthering our understanding of possible functions of RNA–protein π-interactions in biology, the present work paves the way to better understand new roles of noncovalent interactions in proteins. As highlighted by the example of modified PUF enzymes in the introduction ( 25 ), an improved working knowledge of the ways amino acids and nucleic acids can interact will permit the design of proteins with specific functions, such as the regulation of RNA sequences ( 67 ) and the controlled modification of nucleic acids ( 68 ). Beyond interactions between canonical amino acids and nucleosides, the greater insight into π–π interactions obtained from this study can be applied to better comprehend and develop ligands and drugs that bind to nucleic acids and/or proteins ( 69 , 70 ).…”
Section: Discussionmentioning
confidence: 99%
“…The specificity of targeted DNA methylation in E. coli was found to be strongly dependent on the intracellular MTase activity, but reducing the DNA binding affinity of the MTase domain had little if any influence on methylation specificity. These results shed new light on data obtained with mutant DNA MTases, where increased specificity of targeted DNA methylation was attributed to the weakened DNA binding affinity of the MTase 20 , 21 , 23 , 24 , 26 , 38 .…”
mentioning
confidence: 58%
“…Specificity of targeted DNA methylation has been a concern during the whole history of this research field 24 , 31 , 32 . Although some of the earlier papers reported acceptable targeting specificity, recent comprehensive studies showed that unintended off-target methylation remains a problem 33 35 .…”
mentioning
confidence: 99%
See 1 more Smart Citation